The Dynamics of Adolescent Relationships and the Disintegration of Moral Regulation: A Study on Teenage Pregnancy in Paremono, Magelang - Cahyani, Ria Nur; Wardana, Amika; Lovendo, Tomy (Jurnal Sosiologi Agama, 2025)
Unplanned pregnancies among teenagers are often perceived merely as a lapse in individual self-discipline. Nevertheless, in Paremono Village, located in Magelang Regency, a community that upholds strong Islamic values, this issue reveals a sociological contradiction. This research seeks to understand why the moral regulations associated with religion fail in deterring risky sexual activities among young people. Employing a qualitative case study method, data were gathered through comprehensive interviews with 20 participants: 10 adolescent girls who are pregnant, 5 parents, and 5 religious leaders. The study's results indicate a breakdown in informal social control structures. Cultural and religious stigmas surrounding sexuality create obstacles to communication within families, resulting in a “reproduction of ignorance.” Consequently, adolescents experience cognitive dissonance: they have theological awareness about what constitutes “sin,” yet lack meaningful moral support to withstand external pressures. Viewed through the framework of Social Learning Theory, the absence of parental and religious guidance is compensated for by peer groups that normalize a liberal dating environment and digital pornography. This research concludes that an abundance of religious symbols does not guarantee moral internalization without engaging in and facilitating open educational discussions. This study suggests enhancing the involvement of religious leaders to reduce the stigma surrounding reproductive health education and to transition the teaching approach from a rigid to a more conversational style.